Increased prevalence of recurrence in squamous cell carcinoma arising from buccal mucosa: A pervasive threat requiring multidimensional perspectives - Thilaga Duraisamy; Ramya Ramadoss; Suganya Panneer Selvam; Sandhya Sundar; Nitya Krishnasamy; Hemashree (Oral Oncology Reports)
Perspective goal: Squamous cell carcinoma (SCC) of the buccal mucosa is at a higher risk of local recurrence. Surgery in this area is complex and frequently results in close or positive margins, which increases the risk of recurrence. A margin distance of less than 1 mm from the tumour is linked to a higher rate of recurrence. Discussion: Anatomic, genetic, environmental, and lifestyle factors contribute to its resurgence. Effective prevention strategies, early detection, and treatment require a multidimensional approach. Understanding genetic, environmental, and socio-cultural factors can help develop effective prevention strategies, improve early detection, and enhance treatment outcomes. Conclusion: Despite advancements in medical technology and awareness campaigns, the aggressive nature of SCC and its adverse impact on patient's quality of life necessitates a comprehensive understanding of its factors. A comprehensive and multidimensional approach is crucial for combating this pervasive public health threat. By integrating this knowledge into prevention strategies, healthcare professionals can work towards reducing the burden of SCC and enhancing patients' quality of life.